Glucose Oxidase Immobilization on TMAH-Modified Bentonite - Ruth Chrisnasari; Zerlina Gabriela Wuisan; Arief Budhyantoro; Restu Kartiko Widi (Indonesian Journal of Chemistry, 2015)
The influence of bentonite modification by tetramethyl ammonium hydroxide (TMAH) on its capability to immobilize glucose oxidase (GOX) was studied. Modification of bentonite was conducted by the adding of 0-5% (v/v) TMAH. The observed results show that the different concentrations of TMAH affect the percentage of immobilized enzyme. The results of this study show that the best concentration of TMAH is 5% (v/v) which can immobilize up to 84.71% of GOX. X-ray diffraction (XRD) and Fourier Transforms Infrared Spectroscopy (FTIR) studies have been carried out to observe the structural changes in bentonite due to TMAH modification. The obtained immobilized GOX show the optimum catalytic activity on reaction temperature of 40-50 °C and pH of 7. The immobilized GOX kinetics at the optimum conditions determined the Km and Vmax value to be 4.96x10-2 mM and 4.99x10-3 mM.min-1 respectively. In addition, the immobilized GOX on TMAH-modified bentonite is stable enough so it could be re-used six times before its activity decreased by 39.44%.